(untitled) (Innovative Technologica: Methodical Research Journal, 2022)
This study of Turkic languages contributes to a deeper understanding of the historical development of the modern Uzbek literary language and its current development. Because the dialects of modern Uzbek literary language are connected with the languages of Kipchak, Oguz and Qarluq groups of Turkic languages. It is known that the number of Turkic-speaking peoples is second only to the Slavic-speaking peoples.